Trypanosoma evansi causes thyroxin imbalance with biochemical alterations in wistar rats - Sivajothi, Sirigireddy; Rayulu, V. C.; Reddy, Bhavanam Sudhakara; Kumari, Karumuri Nalini Kumari Nalini (Journal of Advanced Veterinary and Animal Research, 2015)
Animals affected with Trypanosoma evansi show rare serum hormonal disturbances. One of the important hormones for livestock is thyroxin, and the level of thyroxin may be reduced during the T. evansi infection. The objective of the study was to investigate thyroxin level during experimentally induced T. evansi infection in Wister albino rats. Wistar albino white rats (n=12) were challenged with the local strain of T. evansi (at 5x105 trypanosomes/animal subcutaneously). At the high parasitemia, blood was collected from the rats, and serum was separated, which was subjected for biochemical evaluation. Decreased total serum thyroxin (2.91 ±0.04 µg/dL) and free thyroxin (1.30 ±0.05 ng/dL) levels (p<0.01) were recorded in T. evansi infected rats as compared to the control group of rats. Along with lowered thyroxin levels, decreased levels of total erythrocyte count, packed cell volume, hemoglobin, total leucocyte count, total serum proteins, albumin and glucose levels were recorded. On the other hand, significant increase (p<0.01) in cholesterol, blood urea nitrogen, serum alkaline phosphatase, serum aspartate aminotransferase, and serum alanine aminotransferase levels were observed. Thus, it is concluded that trypanosomiasis induces stress on rat, which have direct effect on thyroid hormone. http://dx.doi.org/10.5455/javar.2015.b68